The little SAS book for Enterprise Guide 4.2 - Slaughter, Susan J.; Delwiche, Lora D.; Safari eBooks (Cary, N.C. : SAS Institute, 2010)
"Helps you quickly become productive in the SAS Enterprise Guide point-and-click environment. A series of carefully designed tutorials help you master the basics of the tasks you'll want to do most frequently. This edition has been completely rewritten and updated with new features for SAS Enterprise Guide 4.2"--Resource description page.
Tutorial A: Getting started with SAS Enterprise Guide -- Tutorial B: Creating reports -- Tutorial C: Working with data in the query builder -- Tutorial D: Joining two data tables together -- Ch. 1: SAS Enterprise Guide basics -- Ch. 2: Bringing data into a project -- Ch. 3: Changing the way data values are displayed -- Ch. 4: Modifying data using the query builder -- Ch. 5: Sorting and filtering data -- Ch. 6: Combining data tables -- Ch. 7: Producing simple list and summary reports -- Ch. 8: Producing complex reports in summary tables -- Ch. 9: Basic statistical analysis -- Ch. 10: Producing graphs -- Ch. 11: Changing output styles and types -- Ch. 12: Adding flexibility with prompts and conditions.
Description based on print version record.
Includes index.
Keywords: SAS (Computer file); Enterprise guide; Mathematical statistics -- Data processing; Business -- Data processing; Electronic books